ANALISIS KUALITAS PELAYANAN AIR, KUANTITAS PEMAKAIAN, DAN KONTINYUITAS PENGALIRAN AIR TERHADAP KEPUASAN PELANGGAN PERUSAHAAN UMUM DAERAH AIR MINUM TIRTA PINANG - KOTA PANGKALPINANG - Hakiki; Ahmad Agin, Arka’a; Oktalina, Gayatria (Jurnal Progresif Manajemen Bisnis, 2019)
Tirta Pinang public water company City of Pangkalpinang as one of the companies that provides public services in the form of public services, quantity requirements, and continuity requirements. Starting from the description above, it is necessary to study through a study to explain the level of satisfaction with the clean water office of Tirta Pinang public water company in terms of indicators of air quality, quantity, and continuity of air flow. The quality of water that is desired is the quality of water that meets the requirements or standards that apply from physical parameters, desired quantity is that that meets the water requirements for a medium city, for water flow continuity must be available 24 hours per day, or 12 hours per day, This is when the community activities take priority in the use of water. To examine the problem, it is done using descriptive analysis method in which the researcher explains about the existing conditions. This type of research is a quantitative descriptive study with a location in the Tirta Pinang public water company’s Office. Source of data used are primary data through interviews and observations, and secondary data taken from documents. The sampling technique uses purposive sampling, the data collection technique uses interviews with customers who come to pay bills to the office and visits to customers’ homes. The number of respondents was 371 respondents from a total of 5148 customers. From the results of the study, customers were satisfied with the services provided by the Tirta Pinang public water company. In other words, in terms of air quality, quantity, and air flowing, Tirta Pinang public water company has been fulfilled.